ANALIS PENERAPAN BLUE OCEANS STRATEGY PADA SERVICE MARKETING MIX TERHADAP KEPUTUSAN PENGGUNAAN JASA GOJEK - Abdul Qadir; zakaria wahab; welly nailis (JEMBATAN, 2017)
The main objective of this research was to determine the effect of service marketing mix to the decision to use services of go-jek. The sample used in this study were 120 respondents from consumer Go-jek. The sampling method used is purposive sampling due to the homogeneity of the consumer. The coefficient of determination show that 53.9% indicates the use of services affected by the decision variable service marketing mix (product, price, place, promotion, people, process,and physical evidence). Data analysis technique used is multiple regression analysis. Results of research showed that service marketing mix decisions affect the use of the service simultaneously. Partially, only the variable price, people, and physical evidence that has a significant influence on the decision to use services of Go-jek. Keyword : service marketing mix, promotion, decision to use services.